Synchronized Accounting - the Vector of Progress and Performance in Economic Entities: Array - Danescu, Magdalena (Acta Universitatis Danubius. Œconomica, 2021)
Synchronous management accounting consists in identifying specific operations that an economic entity can perform internally to find the most efficient solutions to eliminate certain dysfunctions in the entire value chain, in creating certain much higher values, which can be shared by all actors in the chain. Synchronous management requires a cultural change, but also a management system and an accounting system. A change in organizational culture that is not supported by an adequate accounting system and relevant performance indicators is inevitably doomed to failure. The new tools, techniques and methods characteristic of synchronized management accounting advocate the abandonment of the paradigm of scientific organization for a new paradigm that considers the economic entity as a system.